STRATEGI CYBER PUBLIC RELATIONS MELALUI INFLUENCER MARKETING DALAM MEMBANGUN BRAND ENGAGEMENT GLAD2GLOW DI TIKTOK - Zalfa Adlina; Riska Apriana; Rama Delly; Muh. Rafi Aflah; Sri Hertimi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
The rapid acceleration of the beauty industry in the digital realm demands the evolution of conventional public relations functions into dynamic Cyber Public Relations (Cyber PR). Amidst the intense competition for consumer attention, the TikTok platform with its For You Page (FYP) algorithm has become the primary battleground utilized by the skincare brand Glad2Glow to foster brand engagement. This study aims to analyze in depth the Cyber Public Relations strategy through influencer marketing in building Glad2Glow's brand engagement on TikTok. The research method employed a qualitative approach with a descriptive netnography (cyber-ethnography) design to naturally observe cyber interaction patterns, supported by in-depth interviews with digital PR practitioners and influencers. The results indicate that Glad2Glow implements a hybrid PR 2.0 communication model by orchestrating three tiers of influencers: macro-influencers as anchors for mass exposure, micro-influencers as deep-content educators, and nano-influencers as drivers of organic reviews. This orchestration successfully triggers a multi-stage conversion of public brand engagement, moving from cognitive (viewing attention), emotional (intimate relationships in the comments section), to behavioral dimensions (active participation in producing User-Generated Content). This study offers a theoretical contribution to the enrichment of cyber PR literature and digital marketing communication, as well as a practical guide for creative industry practitioners in optimizing short-form video algorithmic ecosystems.